Authenticity in the Perspective of Sport Tourism: Some Selected Examples - Hurych Emanuel (Sciendo, 2017)
Authenticity is usually understood as something similar to truth, or as a kind of ability of one "to be oneself". However, for the philosophical approach, authenticity presents a more complex and complicated term. This conception has been followed in existentialism and fundamental ontology, where it has been examined and analyzed in depth (especially by Martin Heidegger). This paper deals with the search for some potentiality of the authentic modus of being through the practice of some forms of sport tourism. We selected and described four model types of sport tourism activities. Then, we designed and selected some factors of authenticity. The evaluation of authenticity within the selected activities according to the factors was applied in a two-round process of evaluation. The results of the process are explained and discussed. In conclusion, authenticity is presented as a concept that is not strongly influenced by outer settings, but is rather strongly connected with personal attunement and individual (or group) perception of the outer world.